2016
DOI: 10.1530/erc-16-0104
|View full text |Cite
|
Sign up to set email alerts
|

New drugs for medullary thyroid cancer: new promises?

Abstract: Medullary thyroid cancer (MTC) is a rare tumor arising from the calcitonin-producing parafollicular C cells of the thyroid gland, occurring either sporadically or alternatively in a hereditary form based on germline RET mutations in approximately one-third of cases. Historically, patients with advanced, metastasized MTC have had a poor prognosis, partly due to limited response to conventional chemotherapy and radiation therapy. In the past decade, however, considerable progress has been made in identifying key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 44 publications
0
20
0
4
Order By: Relevance
“…This underscores the urgent issue of identifying new drug targets for treating medullary thyroid carcinomas. Because RET mutations (denoted RET(ϩ)) have been well documented in hereditary medullary thyroid carcinoma and in a significant fraction of sporadic medullary thyroid carcinoma, inhibitors of RET are proven for clinical use in treating these patients (37,38). Conceivably, tumor cells would eventually develop resistance to RET inhibitors as has been observed in other types of cancers that are initially sensitive to receptor tyrosine kinase inhibitors (39).…”
Section: Discussionmentioning
confidence: 99%
“…This underscores the urgent issue of identifying new drug targets for treating medullary thyroid carcinomas. Because RET mutations (denoted RET(ϩ)) have been well documented in hereditary medullary thyroid carcinoma and in a significant fraction of sporadic medullary thyroid carcinoma, inhibitors of RET are proven for clinical use in treating these patients (37,38). Conceivably, tumor cells would eventually develop resistance to RET inhibitors as has been observed in other types of cancers that are initially sensitive to receptor tyrosine kinase inhibitors (39).…”
Section: Discussionmentioning
confidence: 99%
“…Selumetinib, a MEK1/2 inhibitor was found to reverse refractoriness to RAI in patients with metastatic DTC (104). Details of clinical trials in thyroid cancer are summarized in Table 1 and can be found elsewhere (105,106). A limitation of targeted therapy is the development of an escape mechanism.…”
Section: Tki Therapy For Advanced-stage Thyroid Cancermentioning
confidence: 99%
“…With the advent of various anticancer drugs, cytotoxic and molecularly targeted compounds have become the first-line standard treatment regimens for most cancer patients when surgery is not an appropriate option [1, 2]. In 2004, it was first reported that a mutation in the epidermal growth factor receptor (EGFR) conferred a clinical response to EGFR tyrosine kinase inhibitors (TKIs) in non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%